Pendampingan UMKM Dapoer Mini di Kelurahan Gunung Anyar Melalui Branding Produk - Dava Praya Syafa Kurniawan; Noor Rizkiyah; Praja Firdaus Nuryananda (Jurnal Informasi Pengabdian Masyarakat, 2023)
Gunung Anyar Village is one of the villages in Gunung Anyar sub-district, Surabaya City, East Java Province, Indonesia. Gunung Anyar village has a lot of potential, especially from an economic point of view. The awareness of MSMEs in Gunung Anyar about the importance of branding is still lacking. The need for assistance regarding branding can reduce these problems. In carrying out branding assistance to MSMEs, knowledge about this matter is also important so that when carrying out mentoring it goes well. The main purpose of branding is to create a product that is different from competing businesses. Through this branding assistance, it is hoped that it can increase revenue from product sales, as well as increase sales competitiveness.